HEROISME AMERIKA DALAM FILM - Winda Primasari (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
Movie is considered as the reflection of reality. Thus, movie is often used as the propaganda tool by some countries, especially America. Through movie, America tries to spread its power and ideology to other countries. This research aims to (1) describe and identifies meanings made by students after watching American heroic movies; (2) find out meanings produced by students toward American he-roic movies. Result shows that students have same perception and meanings to-ward American heroic movies that is they managed to represent America’s hero-ism as the saviour of mankind.